Analisis Faktor-Faktor Yang Mempengaruhi Produktivitas Karyawan Cv. Comed Pro Di Solo - Hadiyanto, Wisnu, Nur Achmad,SE,M.Si (2016)
This study aimed to analyze the influence of motivation, work environment, level of education, and work experience on productivity of employee CV. Comed Pro Solo. In this study using regression analysis techniques, the classic assumption test, and test the validity and reliability. The sample was 42 respondents working in the CV. Comed Pro Solo. The results obtained showed that in partial motivation and work environment has a significant influence on productivity of employee because it has a smaller 0,020 and 0,010 than 0.05. While the level of education and work experience no significant effect on productivity of employee due has a probability of 0.644 and 0.188 greater than 0.05. Simultaneously motivation, work environment, level of education and work experience have a significant effect on productivity of employee.